ANALISIS USAHATANI DAN KEMAMPUAN MEMBAYAR KREDIT PADA PETANI KARET EKS UPP TCSDP TALUK KUANTAN SUB UNIT KUANTAN TENGAH - Elveni Guspiarni; Syaiful Hadi; Jum’atri Yusri (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
The objectives of this research are to analysis of rubber  farming system and the ability to pay credit of ex UPP TCSDP rubber plantation in Sub Unit Kuantan Tengah, Kuantan Singingi Regency. Survey method was conducted in 3 villages, involved Kopah, Seberang Taluk and Pulau Aro rubber farmers. In each village taken 10 people into bringing its total respondents 30 respondents. The results showed that the average production in rubber plantations Ex TCSDP UPP is ojol much as 2,146 kg/year with the ojol productivity of 1,966 kg/ha/year. The rubber plantations of non TCSDP average production is by ojol 3,966 kg/ha/year and productivity amounted to 2,012 kg/ha/year. Credit payments of all agricultural and non agricultural income of farmers, farmers were 17 (56.67%) were able to pay the remaining credit TCSDP with an average household income of farmers amounted to Rp. 55.074.077/year, while the farm household expenditure of Rp. 19.793.387/year. Keyword :rubber farmers, credit, productivity, TCSDP